Numerical Modelling of Free Surface Agitation in a Coastal Lagoon by Roadway Path Influence. (18th February 2023) - Herrera, Israel E.; Torres, Franklin M.; Moreno, Jatziri Y.; Gutierrez, José M.; Saldaña, Noé
Abstract : The development and construction of highway infrastructure are essential in developing countries, whereas its layout and construction sometimes interact with the coastal environment. One problem to attend to is that the outline and geometry designs impact as little as possible on the hydrodynamic circulation of coastal bodies in order to alter the associated ecosystem as little as possible. The study area is located in the north of Colombia, and is made up of a continental coastal zone (Mallorquín Lagoon) and a marine zone (Caribbean Sea), in which a highway is projected that provides communication between two locations. This study presents the application of a numerical model previously developed and modified by the Berkhoff equation, which is developed in a finite difference scheme and has been validated and applied in different works in coastal and fluvial shallow water areas. The application of the model was carried out in a hydrodynamic circulation research project for a one-way highway through a coastal lagoon, where the knowledge of the magnitude of the incident wave height in the structure of the road body is necessary for the design, protection elements, and road geometry. Two numerical simulation scenarios were carried out, specifying normal conditions and extraordinary wave conditions in the month of November with a simulation time of 15 days, obtaining the velocity field associated with coastal currents, waves, and wave modification phenomena, such as refraction, diffraction, and reflection, which provide the height of the incident wave on the highway and the recirculation patterns in the coastal lagoon to identify alterations in the ecosystem. The results of the wave height in each scenario and the velocity field provide values to be used in the design, type of armor, and dimensions of the protection works required for the proper functioning of the road structure.